Pendampingan Belajar Siswa Melalui Pembelajaran Multimodal Untuk Meningkatkan Kemampuan Siswa di Masa Pandemi Covid-19 - Riza Faishol; Imam Mashuri; Eka Ramiati; Idi Warsah; Hikmah Nur Laili (Institut Agama Islam Negeri Bengkulu, 2021)
This devotional activity is motivated by the number of parents who cannotaccompany their children to learn from home during the pandemic for various reasonsand occupations. Another obstacle is that students are unable to understand the subject matter independently, the support facilities are lacking, some students and parentscannot operate gadgets, there are even students who do not have gadgets that hinder infollowing online learning. Therefore, this student learning mentoring is done with the aim to increase the activeness, creativity, and confidence of students in learning. The method of implementation of mentoring is carried out in several stages, namely preparation, implementation of mentoring, and evaluation. With this innovation of multimodal learning, it is proven to be very helpful for students who were previously quiet, shy, and lacking confidence. After participating in this mentoring process, the participants become more active, creative, and have high confidence.